Correction to: Health-related quality of life in girls and boys with juvenile idiopathic arthritis: self- and parental reports in a cross-sectional study - Veronica Lundberg; Viveca Lindh; Catharina Eriksson; Solveig Petersen; Eva Eurenius (BMC, 2018)
Following publication of the original article [1], the authors reported an error in the data of their article: one girl was by mistake scored as a boy. The authors have made new analyses of the corrected data. The corrected data and the new analyses are listed in this Correction.